2016
DOI: 10.1371/journal.pone.0160139
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Anti-Reflux Therapy for GERD with Respiratory Symptoms: A Study Using Multichannel Intraluminal Impedance-pH Monitoring

Abstract: Background/AimsRespiratory symptoms are often associated with gastroesophageal reflux disease (GERD). Although the role of multichannel intraluminal impedance–pH (MII-pH) monitoring in GERD is clear, little is known regarding the characteristics of patients with respiratory symptoms based on MII-pH monitoring and anti-reflux therapy. We evaluated a cohort of GERD patients to identify the MII-pH parameters of GERD-related respiratory symptoms and to assess the anti-reflux therapy outcomes.MethodsWe undertook a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…25 Salivary pepsin level can quickly distinguish true reflux with non-reflux diseases, and is important for the diagnosis of GERD patients with predominant respiratory symptoms. [14][15][16][17]26 In this study, the positive rate of detecting EES was 68.2%, which was consistent with the observation of a previous study, 24 suggesting that salivary pepsin is of certain diagnostic value for the diagnosis of EES. In addition, the salivary pepsin level and positive rate in the BE group were significantly higher than those in the HC group in the present study, suggesting that pepsin reflux does play a significant role in the process of BE formation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…25 Salivary pepsin level can quickly distinguish true reflux with non-reflux diseases, and is important for the diagnosis of GERD patients with predominant respiratory symptoms. [14][15][16][17]26 In this study, the positive rate of detecting EES was 68.2%, which was consistent with the observation of a previous study, 24 suggesting that salivary pepsin is of certain diagnostic value for the diagnosis of EES. In addition, the salivary pepsin level and positive rate in the BE group were significantly higher than those in the HC group in the present study, suggesting that pepsin reflux does play a significant role in the process of BE formation.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, a study found more episodes of reflux in patients with EES than those without reflux symptoms by 24-hour pH monitoring, among which episodes of reflux could be detected in 49.2% of patients with respiratory symptoms. 24 Therefore, for patients with long-term chronic dry cough, pharyngitis, asthma, hoarseness, and other respiratory manifestations and unresponsive to routine treatments, the possibility of EES should be considered. 25 Salivary pepsin level can quickly distinguish true reflux with non-reflux diseases, and is important for the diagnosis of GERD patients with predominant respiratory symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the integrity of the hernia repair, QOL after surgery is also an important consideration, and global measures of outcome that integrate improvements in symptoms and post-surgical side effects should also be considered when determining surgical success [ 29 ]. It is well known that laparoscopic fundoplication for GERD can significantly improve QOL [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the Stretta procedure was equal to ARS in controlling extraesophageal manifestations of GERD [ 25 ]. By contrast, Stretta was inferior to ARS for typical and respiratory symptoms associated with GERD in two other studies [ 26 , 27 ]. Unfortunately, no RCTs to date have compared both the modalities.…”
Section: Radiofrequency Ablationmentioning
confidence: 87%